Participación ciudadana y espacio popular urbano en Medellín : entre ciudadanía insurgente y programas de planeación participativa y urbanismo social - Comuna 1 y Comuna 13. Una reflexión comparativa (2012)
ABSTRACT: Recent changes in public management and urban planning in Medellin (Colombia) are presented most of the time as an undifferentiated whole, where the municipal government has taken the initiative and the local population goes behind him. The fact is that, despite the general dynamic of the city, each Comuna (political-administrative division of the city) has its own logic and way of engage the actions and municipal policies. This is the Comuna 1 case, where we can see, through municipal programs as the Participative Planning and Budgeting and Integrated Urban Projects (PUI), the expression of a kind of insurgent citizenship, who, by means of a dialectic of cooperation and conß ict with the municipal government, has been able to build a Local Development Plan, which propose guidelines of urbanism and popular housing for the commune inhabitants. Slightly different is the Comuna 13 case, a complex scenario where despite of the social urbanism and having the biggest social investments in the municipality in the last 8 years, the levels of violence are been reluctant to fall, hiding in the background illegal and politicking practices Þ ghting against the local state and grassroots organization for the territorial control. It shows how an urban project, social or participative, if does not politically recognize the local population, their differences and their spaces, will only be one more physical piece that does not develop the institutionality and democratic local culture.